Optimation of Hematopoietic Stem Cells’ Culture Medium: A Review - prasetyadi prasetyadi (Journal of Stem Cell Research and Tissue Engineering, 2020)
Hematopoietic stem cells (HSCs) usage has numerous potential benefits for basic and clinical research.  Growing interest in this field is caused by possible HSCs application   to cure   various   hematologic   diseases, malignancies, immunodeficiency diseases, and inborn errors of metabolism.  Although the demand of HSCs is increasing, ex vivo culture of HSCs has various medium compositions. This article focuses on HSCs’ culture medium optimation in different medium supplements, which might overcome non-optimal HSCs culture results. Literature searching was conducted in PubMed and google scholar database. Paper selection processes were done by author separately and studies which met the eligible criteria were included in this review. A total of 53 relevant articles were identified and 11 articles that met the eligible criteria were included in this review. There are two main types of supplement, cytokines and non-cytokines.  In cytokines addition, 7 studies generally show that the supplement support HSCs expansion.  The addition of non-cytokines supplements has more diverse   result in studies.   Positive   results   with various   effectivity   in CD34+ expansion were shown in 3 studies, while one study shows a negative result. Medium supplementation must be explored more to find best substances which can optimize   HSCs   culture.   Further   research   using   non-cytokines   substance   shall   be conducted regarding its various effect and might give us a big opportunity to find an optimal condition for HSCs culture.